2015
DOI: 10.1111/bjd.13525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myasthenia gravis and associated autoantibodies in paraneoplastic pemphigus and their correlations with symptoms and prognosis

Abstract: MG is a complication of PNP. Anti-AChR and anti-AChE antibodies are prominent in patients with PNP, especially those with dyspnoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 59 publications
(118 reference statements)
1
38
0
1
Order By: Relevance
“…Our case findings support the proposed theory that cell‐mediated autoimmunity initially induces interface and lichenoid dermatitis, then promotes the exposure of self‐antigens and development of progressive humoral autoimmunity through the epitope‐spreading phenomena . Myasthenia gravis frequently occurs in patients with PNP . Anti‐AChR antibody levels might affect the patient's survival …”
Section: The Results Of Enzyme‐linked Immunosorbent Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Our case findings support the proposed theory that cell‐mediated autoimmunity initially induces interface and lichenoid dermatitis, then promotes the exposure of self‐antigens and development of progressive humoral autoimmunity through the epitope‐spreading phenomena . Myasthenia gravis frequently occurs in patients with PNP . Anti‐AChR antibody levels might affect the patient's survival …”
Section: The Results Of Enzyme‐linked Immunosorbent Assaysmentioning
confidence: 99%
“…3 Myasthenia gravis frequently occurs in patients with PNP. 4 Anti-AChR antibody levels might affect the patient's survival. 4 Cases of lichenoid PNP without autoantibodies have been reported.…”
mentioning
confidence: 99%
“…The pathogenesis is thought to be due to the production of antibodies against tumor‐derived antigens; the antibodies may attack components sharing the same or a similar epitope 8. Wang et al 9 reported that MG is a complication of PNP. Ocampo–Candiani et al 10 reported a case in which PNP associated with FDCS showed a good response to a treatment plan that included dexamethasone, surgery, and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been several case reports of patients with PNP associated with MG and thymoma; or PNP with MG, Castleman tumour and bronchiolitis obliterans. 11,12 In this issue of the BJD, Wang et al 13 report on a large-scale study of neurological symptoms and MG-related autoantibodies in 58 Chinese patients with PNP, demonstrating a clear association of MG and PNP for the first time.…”
Section: Original Article P 968mentioning
confidence: 99%
“…The authors concluded that MG is a frequent complication of PNP and that autoantibodies to the acetylcholine receptor and acetylcholinesterase are frequently detected in sera from patients with PNP. Thus, the study by Wang et al 13 indicates that autoantibodies produced in patients with PNP not only target epidermal proteins but also extend to other antigens in neural and bronchial tissues. In addition, PNP tends to affect visceral diseases, causing MG and bronchiolitis obliterans as well as mucocutaneous lesions.…”
Section: Original Article P 968mentioning
confidence: 99%